Spatio-temporal variability of groundwater depth in the eghlid aquifer in southern iran (2013)
Groundwater is the main water source for domestic and agricultural use in Eghlid, a city located in Fars province in southern Iran. Here, spatial and temporal changes in groundwater depth were monitored by using geostatistical methods at 41 observation wells in Eghlid during the wet and dry seasons of 1997, 2003 and 2010. Experimental semivariograms were calculated and modeled with the GS+ (Gamma Design Software, Plainwell, Michigan USA),and groundwater depth was inter- polated by using the ordinary kriging (OK), simple kriging (SK) and inverse distance weighting (IDW) methods within the GIS environment. Moreover, groundwater depth fluctuations over 13 years (from 1997 to 2010) were calculated and mapped for wet and dry periods. The groundwater depth in the Eghlid aquifer exhibited a strong spatial correlation that followed a spherical model for three years. However, the spatial correlation distance was larger for both seasons in 1997 (grea- ter than 27 km) than in 2003 (22 to 27 km) and 2010 (23 to 25 km). The cross-validation results indicated that OK resulted in the lowest root mean square error (RMSE) and mean error (ME) and was the most appropriate method for interpolating groundwater depth. Therefore, OK was used to map the spatial distribution of the groundwater depth over the study area. The resulting maps indicated that the spatial variability of groundwater depth was greater during the wet season than during the dry season over three years. In addition, changes in the depth to groundwater occurred more slowly during the wet seasons than during the dry seasons. Furthermore, the ground water depth decreased slightly from 1997 to 2003 and decreased considerably (2-13 m) from 2003 to 2010. Moreover, the decrease in the groundwater depth was more notable in the central to west and southern regions of the aquifer. Thus, these regions are critical and should be managed carefully to optimize groundwater resource exploitation. ResumenLas aguas subterráneas son la principal fuente hídrica para el uso doméstico y agrícola en Eghlid, una ciudad ubicada en la provincia de Fars, al sur de Irán. Aquí, los cambios temporales y espaciales en la profundidad de las aguas subterráneas se sondean a través de métodos geoestadísticos en 41 pozos de observación en Eghlid durante las estaciones de verano e invierno de 1997, 2003 y 2010. Se calcularon semivariogramas experimentales y se modelaron con el programa informático GS+, y la profundidad de las aguas subterráneas se interpolaron por el uso de krigging ordinario (OK), krigging simple (SK) y mé- todos de ponderación de distancia inversa (IDW) dentro del ambiente GIS. Sin embargo, la fluctuación de profundidad de las aguas subterráneas en cerca de 13 años (de 1997 a 2010) se calculó y se mapeó para las temporadas húmeda y seca. La profundidad de las aguas subterráneas en el acuífero de Eghlid muestra una fuerte correlación que sigue un modelo esférico de tres años. Sin embargo, la distancia de correlación espacial fue mayor para ambas temporadas en 1997 (mayor que 27 km.) y en 2003 (22 a 27 km.) y 2010 (23 a 25 km.). Los resultados de validación cruzada indicaron que el producto OK en la raíz cuadrada media de desviación más baja (RMSE) y Error Medio (EM) fueron los métodos más apropia- dos de interpolación de la profundidad de aguas subterráneas. Por lo tanto, el OK fue usado para mapear la distribución espacial de la profundidad de las aguas profundas en el área de estudio. El resultado de los mapas indican que la variabilidad espacial de la profundidad de aguas subterráneas fue mayor durante la temporada húmeda que durante la temporada seca en tres años. Adicionalmente, la profundidad de las aguas subterráneas fue menor durante la temporada húmeda que durante la temporada seca. Además, el nivel de las aguas profundas cedió ligeramente desde 1997 a 2003 y cayó considerablemente (de 2 a 13 metros). Además, el decrecimiento en el nivel de las aguas profundas fue más notable en las regiones de oeste, centro y sur del acuífero. Por ende, estas regiones son críticas y se deben manejar cuidadosamente para optimizar el recurso de explotación de las aguas subterráneas.